Type-II heterostructure of semiconducting CdS nanoparticle-ZnO nanoflake arrays for visible light dependent enhanced photocatalytic activity - Amit Kumar Bhunia (Scientific Reports)
Abstract Type-II heterostructure semiconductors are very attractive for optoelectronics, environmental and energy-related applications. In this report, the heterostructure (Hs) semiconductor nanocrystalline CdS-ZnO was grown by a cost-effective chemical precipitation method and study of photocatalytic performance from the view of type-II semiconductor heterostructure. The array of nano flake (NF)-particle (NP) morphology of the Hs was observed from FESEM images. Different optical parameters like refractive index, optical conductivity, energy functions, and others were studied from UV-Vis spectroscopy. Tuning of the excitonic peaks (355 nm to 464 nm), band gap energy (3.78 eV to 2.8 eV), and Urbach energy (1 eV to 2.35 eV) have been observed from optical spectroscopy. The crystal phase matching in the Hs has been verified from the observed hexagonal wurtzite structure of both CdS NPs and ZnO NPs. The greater ultrafast life time of the CdS NP-ZnO NF Hs (59 nS) was found compare with pure CdS NPs (17 nS) and ZnO NPs (4.41nS). The observed room temperature current in the heterostrcture enhanced heavily compare with pure ZnO NPs at any voltage (-10 V to + 10 V). A photocatalytic degradation test showed that the highest efficiency (≈ 95%) degradation of MB within 28 min was obtained using type II CdS NP-ZnO NF heterostructure (Hs) semiconductors compare with pure ZnO NPs (75%) and pure CdS NPs (83.5%) under visible light irradiation. This highly efficient activity of the HS was induced by enhanced charge separation and interfacial charge transfer in nanocrystal heterostructure semiconductors.